PERBEDAAN KADAR TUMOR NECROSIS FACTOR-Î± PADA PENDERITA HEPATITIS KRONIS DAN KARSINOMA HEPATOSELULER - , Tri Hartanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The increased levels of TNF-Î± is associated with hepatic inflammation, necrosis, and liver failure because TNF-Î± is formed as a response to tissue injury and also associated with the increased of cell cycle progression and oxidative stress. The high level of TNF-Î± is associated with carcinogenesis. Methods: This is a cross sectional study. Subjects of this study were patients with Chronic Hepatitis and Hepatocellular Carcinoma who were treated either at polyclinic of Internal Medicine or at ward of Internal in Dr. Sardjito Central General Hospital and met the inclusion criteria. The comparison of TNF-Î± level in patients with Chronic Viral Hepatitis and Hepatocellular Carcinoma was analyzed using t-test for normal distributed data and Mann-Whitney U test for non-normal distributed data. Data analysis was performed using computerized analysis. The difference was significant if p< 0,05 with 95% confidence intervals. Results: From 18 subjects with Chronic Hepatitis and 18 subjects with Hepatocellular Carcinoma, the average of TNF-Î± levels in subjects with Chronic Hepatitis is 16,51Â±2,55 ng/ml while the average of TNF-Î± levels in those with Hepatocellular Carcinoma is 90,22Â±26,90 ng/ml. This results are statistically significant (p< 0,001). Conclusions: This study suggests that the average of TNF-Î± levels in subjects with Hepatocellular is significantly higher than in those with Chronic Hepatitis.